Dynamic approach for mono- and di-fermentation of black liquor and livestock wastewater for 2-bio-(H2&CH4) production. (February 2021) - Tawfik, Ahmed; Hassan, Gamal K.; Yu, Zhong; Salah, Hala A.; Hassan, Marwa; Meng, Fangang
Abstract: Mono-and di-fermentation of black liquor (BL) and livestock wastewater (LW) was extensively investigated in batch assay experiments. Methane production was the dominant in mono-fermentation of BL and partially co-digested with LW (90% BL+10% LW). Increasing the fraction of LW in the feedstock shifted the microbial activities from biomethanisation into bio-hydrogen generation process. The hydrogen potential (A) was significantly increased from 468 ± 12 to 969 ± 10 ml at increasing the LW ratio in the di-fermentation process from 30% LW + 70% BL to 50% LW + 50% BL. The enzymes activities of α-amylase, xylanase, CM-cellulase, polygalacturonase and protease were maximized at a levels of 420 ± 2.5, 509 ± 5.4, 560 ± 3.9, 686 ± 7.9 and 127.2 ± 6.3 U/100 ml respectively for di-fermentation of 50% LW + 50% BL. Similarly, the valerate (HVa), butyrate (HBu) and acetate (HAc) was highly increased in the digestate of 50% LW + 50% BL up to 654 ± 122.9, 2464.6 ± 67.9 and 657 ± 11.8 mg/l respectively. The Methanobacterium and Methanosaeta were dominated for 10% LW + 90% BL and hydrogen producers i.e., Clostridium, was the major for di-fermentation of the batches containing 50% LW + 50% BL. Graphical abstract: Image 1 Highlights: The pathway of metabolites products and the gas type production is substrate dependent. Di-fermentation of livestock wastewater and black liquor enhanced the enzymes activities. The IC50 was relatively low and antioxidant activity was high for di-fermentation process. Di-fermentation process reduces the negative impact of total phenolic compounds. Low fraction of black liquor in the feed stock enhanced the H2 yield in di-fermentation.